An Analysis of Learners’ Intentions Toward Virtual Reality Learning Based on Constructivist and Technology Acceptance Approaches - Huang, Hsiu-Mei; Liaw, Shu-Sheng (International Review of Research in Open and Distributed Learning, 2018)
Within a constructivist paradigm, the virtual reality technology focuses on the learner's actively interactive learning processes and attempts to reduce the gap between the learner’s knowledge and a real-life experience. Recently, virtual reality technologies have been developed for a wide range of applications in education, but further research is needed to establish appropriate and effective learning techniques and practices to motivate meaningful learning. Results showed that perceived self-efficacy and perceived interaction are two crucial factors affecting perceived ease of use, perceived usefulness and learning motivation. Furthermore, learning motivation is also a predictor to affect perceived usefulness. After that, perceived ease of use, perceived usefulness, and learning motivation are three important factors affecting learner intention to use the virtual reality learning environment.